Reasons and influential recommendations associated with HPV vaccination among Chinese college students in the USA. Issue 6 (31st August 2021) - Tung, Wei-Chen; Lu, Minggen; Langowski, Joey; Qiu, Xiangwen
Abstract: Objectives: To evaluate (a) reasons for not receiving recommended doses of the human papillomavirus (HPV) vaccine, (b) the most influential recommending source in getting the HPV vaccine, and (c) associated factors among Chinese college students in the United States. Methods: A cross-sectional design utilizing a structured self-report questionnaire was used. Participants: A network sample of 449 participants aged 18 or older completed the survey between March and May of 2018. Results: Only 172 participants (38.3%) had received the HPV vaccine. The most common reason was that participants had never received recommendations from healthcare providers regarding HPV vaccines. Recommendations from doctors were the most cited source in deciding HPV vaccine uptake. Factors associated with reasons and recommendation sources included attitudes toward HPV, gender, school year, age, major, and health insurance. Conclusions: Healthcare providers play an important role in promoting HPV vaccination among Chinese college students. More research is needed for this understudied population.